Vìdrodžennâ ta evolûcìâ mìscevogo samovrâduvannâ v Ukraїnì - Gural′, Pavlo (Wydawnictwo Uniwersytetu Wrocławskiego, 2012)
In this article I concentrate mostly on analyze of the renaissance and evolution of the selfgovernment in independent Ukraine, keeping in mind all basic legislative acts, which regulate this complicated and controversial process, starting on 7th December 1990 and continuing until today.
Keywords: Ukraine; self-government; evolution of the self-government